109k views
2 votes
Which of the following equations is equivalent to s=πr^2h

User Kuchi
by
5.9k points

2 Answers

2 votes

Answer:

The equation
h=(s)/(\pi r^2) is equivalent to
s=\pi r^2h. The correct option is B.

Explanation:

The given equation is


s=\pi r^2h

Divide both sides by
\pi r^2 to isolate h.


(s)/(\pi r^2)={\pi r^2h}{\pi r^2}

Cancel out common factors.


(s)/(\pi r^2)=h

Therefore the equation
h=(s)/(\pi r^2) is equivalent to
s=\pi r^2h. The correct option is B.

User Chris Rymer
by
5.5k points
5 votes

Answer:

h = s / π.r²

Explanation:

the given equation is s = π.r².h

Now if we have to calculate the value of h from the given formula then we will solve it so that h remains alone on one side of the equation.

This only possible when we divide term on both the sides by π.r²

s/π.r² = π.r².h/π.r²

h = s / π.r²

Therefore h = s / π.r² is the right option.

User Paludis
by
5.6k points